PENGARUH SENAM OTAK TERHADAP TINGKAT DEPRESI PADA LANSIA DI PANTITRESNA WERDHA BUDI MULIA 2 CENGKARENG JAKARTA BARAT - Suzanna Fabella Putri; Siti Malkah Kamilah (STIKes IMC Bintaro, 2022)
According to WHO, elderly are men and women who have reached the age of 60-74 years. The developing country with the fastest growing number of elderly people in Southeast Asia is Indonesia (Dewi, 2014). The increase in the number of elderly people is also followed by an increase in health problems and a decreasein the welfare of the elderly people related to the aging process. According to Goyal & Kajal (2014) mental health problems experienced by the elderly are depression and anxiety. depression is a mental disorder or disorder characterized by mood swings, loss of pleasure or interest, feelings of guilt, sleep and eating disorders and decreased concentration. One of the therapies that can be done is brain gym, which is included in the treatment of non-pharmacological depression. The purpose of this study was to determine the effect of brain gym on the level of depression in the elderly at Panti Tresna Werdha Budi Mulia 2 Cengkareng, West Jakarta. This research is a quantitative study using the method Quasi Experiment Designwith the One Group Pretest-Posttest design. The research measuring instrument used the Geriatric Depression Scale (GDS) -15 questionnaire. The population in this study were all elderly at Panti Tresna Werdha Budi Mulia 2 Cengkareng, West Jakarta who suffered from depression as many as 50 elderly, with a total sample of 24 elderly. Based on the research, the results of the analysis using the Wilcoxon Signed Rank Test obtained a p value of 0.000, which means that there is an effect of brain gym on the level of depression in the elderly at Panti Tresna Werdha Budi Mulia 2, Cengkareng, West Jakarta.